2021
DOI: 10.3389/fphar.2020.568659
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Pharmacoepidemiology: A Systematic Review. Part 2–Comparison of the Performance of Artificial Intelligence and Traditional Pharmacoepidemiological Techniques

Abstract: Aim: To summarize the evidence on the performance of artificial intelligence vs. traditional pharmacoepidemiological techniques.Methods: Ovid MEDLINE (01/1950 to 05/2019) was searched to identify observational studies, meta-analyses, and clinical trials using artificial intelligence techniques having a drug as the exposure or the outcome of the study. Only studies with an available full text in the English language were evaluated.Results: In all, 72 original articles and five reviews were identified via Ovid M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Sessa et al has proposed the use of artificial intelligence for performing data-driven retrieval of predictors and their nonlinear relationship for the outcome using real-world data. 1,[92][93][94][95][96] Such an approach can potentially lead to the identification of risk factors that can further undergo to pharmacological substantiation using available scientific evidence, clinical reasoning, and, in special circumstances, pharmacokinetic and pharmacodynamic considerations. In fact, it is not unusual to have pharmacometric models lacking risk factors for altered pharmacokinetics/pharmacodynamics.…”
Section: Pharmacological Substantiationmentioning
confidence: 99%
“…Sessa et al has proposed the use of artificial intelligence for performing data-driven retrieval of predictors and their nonlinear relationship for the outcome using real-world data. 1,[92][93][94][95][96] Such an approach can potentially lead to the identification of risk factors that can further undergo to pharmacological substantiation using available scientific evidence, clinical reasoning, and, in special circumstances, pharmacokinetic and pharmacodynamic considerations. In fact, it is not unusual to have pharmacometric models lacking risk factors for altered pharmacokinetics/pharmacodynamics.…”
Section: Pharmacological Substantiationmentioning
confidence: 99%
“…According to the existing cases, arti cial intelligence (AI) has been applied to meta-analysis, which is used to balance a quick time to production with reasonable data quality assurances [68]. In addition to quickly acquiring and processing data, AI is also applied to recognition and prediction [69,70]. The bias risk of each link in the clinical trial design process will signi cantly affect the trial bias risk of meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ovid MEDLINE (from 01/01/2019 to 2022/08/22) was searched, along with the reference lists in the reviews identified with our research query ( Supplementary Table 1 ). Search terms included in the query have been previously used in the context of systematic reviews of AI/ML models and were described by Sessa et al elsewhere ( 15 , 16 ). This review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines ( 17 ).…”
Section: Methodsmentioning
confidence: 99%